EVALUATION OF LECTURER PERFORMANCE (REVIEWED FROM CERTIFICATION AND WORK EXPERIENCE IN THE SULTHAN THAHA SYAIFUDDIN STATE ISLAMIC UNIVERSITY JAMBI) - Zuhri, Firdaus (Dinasti International Journal of Management Science, 2019)
The purpose of this study was to determine the performance of lecturers in terms of certification and work experience at Sulthan Thaha Syaifuddin State Islamic University Jambi. This study uses a comparative quantitative approach or expost-facto, where two-way ANAVA as a statistical analysis method is used to prove the causal relationship between variables. The research hypothesis that was built was that lecturer certification, work experience affect lecturer performance. Random sampling is a sampling technique used on 96 lecturers as respondents. The results showed that lecturer certification, work experience affect the performance of lecturers.